SHAIKH NURUDDIN AR-RANIRI'S EDUCATION IDEA AND ITS UPDATE IN THE MODERN ERA - Iwan Azis Maulana (Education Studies and Teaching Journal (EDUTECH), 2025)
This research is motivated by the urgency of re-examining the legacy of educational thought by Shaykh Nuruddin ar-Raniri (1590–1658) to respond to the challenges of contemporary Islamic education; the focus of the study is the analysis, synthesis, and development of ar-Raniri's ideas so that they can be actualized in current educational practices. The research objectives are (1) to describe ar-Raniri's educational ideas, (2) to examine their relevance to the demands of modernizing Islamic education, and (3) to formulate an applicable actualization framework. The method used is a qualitative literature study with a review of ar-Raniri's primary texts and a review of recent secondary literature (including research from 2020–2025), as well as a qualitative-descriptive analysis to synthesize the findings. The results and discussion show that the core of ar-Raniri's thoughts is the integration of knowledge, morality, and spirituality; attention to a holistic curriculum that combines religious knowledge and rationality; and pedagogical principles that emphasize character building. Synthesis with contemporary practices recommends strengthening value-based curricula, contextual and dialogical methods, and improving educator competencies as steps to actualization, while the main obstacles are limited mastery of classical texts and the influence of secular educational paradigms. In conclusion, the educational thinking of Sheikh Nuruddin ar-Raniri remains relevant and can be actualized in contemporary Islamic education through the formulation of value-oriented curricular policies and educator training.